Coinfecciones bacterianas causantes de enfermedad diarreica aguda, en el Instituto Nacional de Salud del Niño - Gonzales Escalante, Edgar (2015)
In the XXI century, diarrheal diseases continue to represent a major public health problem. According to the records of the World Health Organization (WHO) in developing countries children under 5 years experience an average of 3.2 episodes of diarrhea per year (1,2). Acute diarrheal disease (ADD), mainly infectious, is a public health problem in Peru because of its high economic, social and family costs; being one of the leading causes of morbidity and mortality in childhood (3).